PERANCANGAN E-COMMERCE PADA VINA JAYA FURNITURE SUNGAILIAT BERBASIS WEB MENGGUNAKAN MODEL FAST - Monica, Amanda (Jurnal Media Informatika dan Teknologi, 2023)
Vina Jaya Furniture Sungailiat store is a business that sells furniture products which were established in 2002. Vina Jaya Furniture store is located in Sungailiat City on Jalan Ruko Pasar Atas No.06 Bangka Belitung. Vina Jaya Furniture Sungailiat store carries out promotional activities through banners or brochures distributed to the public. Sales transactions are still carried out conventionally and do not yet use an information system. So research was conducted to overcome this problem to increase the selling power of the Vina Jaya Furniture Sungailiat Store. This study uses the FAST model stages, object-oriented programming methods, and system modeling with UML. The results of this study were able to increase the selling power of the Vina Jaya Furniture Sungailiat Store and make it easier and faster for buyers or managers to make buying and selling transactions. Sales, originally planned to be 5 transactions per day, can be increased to start from 7 trades per day using the designed system. From the results of system functional testing, it can be concluded that the designed system is suitable for use by buyers and store managers. From the designed system, the promotion and marketing area can be wider Keywords: FAST, Furniture, E-commerce